Application of domestic multi-port robot-assisted surgery system in pancreatic surgery - LI Jingfeng, SHI Yusheng, DENG Xiaxing, PENG Chenghong, SHEN Baiyong (Waike lilun yu shijian)
With the development of surgery and technology, robot-assisted pancreatic surgery has gradually become a popular choice for surgeons, and is favored by patients and their families. As the first pancreatic disease treatment center in China to carry out robot-assisted pancreatic surgery, the author's team has unique experience and insight into robot-assisted pancreatic surgery. With the updating and domestication of surgical robots, the domestic multi-port robot-assisted surgical system has begun to be applied in clinical practice. The paper gave an overview of the development of domestic multi-port robotic surgical system in the clinical practice of pancreatic surgery.